2000
DOI: 10.1006/viro.2000.0333
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Clone of Simian-Human Immunodeficiency Virus (ΔvpuSHIVKU-1bMC33) with a Truncated, Non-Membrane-Bound Vpu Results in Rapid CD4+ T Cell Loss and Neuro-AIDS in Pig-Tailed Macaques

Abstract: We report on the role of vpu in the pathogenesis of a molecularly cloned simian-human immunodeficiency virus (SHIV(KU-1bMC33)), in which the tat, rev, vpu, env, and nef genes derived from the uncloned SHIV(KU-1b) virus were inserted into the genetic background of parental nonpathogenic SHIV-4. A mutant was constructed (DeltavpuSHIV(KU-1bMC33)) in which 42 of 82 amino acids of Vpu were deleted. Phase partitioning studies revealed that the truncated Vpu was not an integral membrane protein, and pulse-chase cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Importantly, we show that a minimal substitution of vif with Previous studies with SIVmac showed that deletion of vpr and nef attenuate viral replication and disease in adult macaques (25,32,42), but that these genes are not required for high-level replication and disease in newborns (8). Furthermore, the HIV-1 accessory gene vpu also contributes to pathogenicity of SHIVs in the macaque host, although it is not essential for SHIV induced AIDS (59,81). We therefore examined whether HSIV-vif would replicate more robustly and cause disease in newborn pig-tails, hypothesizing that the lack of activity of the HIV-1 accessory genes may account for the attenuated phenotype in the juvenile animals.…”
Section: Discussionmentioning
confidence: 54%
“…Importantly, we show that a minimal substitution of vif with Previous studies with SIVmac showed that deletion of vpr and nef attenuate viral replication and disease in adult macaques (25,32,42), but that these genes are not required for high-level replication and disease in newborns (8). Furthermore, the HIV-1 accessory gene vpu also contributes to pathogenicity of SHIVs in the macaque host, although it is not essential for SHIV induced AIDS (59,81). We therefore examined whether HSIV-vif would replicate more robustly and cause disease in newborn pig-tails, hypothesizing that the lack of activity of the HIV-1 accessory genes may account for the attenuated phenotype in the juvenile animals.…”
Section: Discussionmentioning
confidence: 54%
“…Our results confirm that S61A did not affect CD4 degradation and the turnover of the protein was decreased. However, these results should be interpreted with caution as a comparison of the Vpu sequence from over 100 HIV-1 isolates revealed that only two Vpu proteins, HXB2 and BRU, had a serine in this position (McCormick-Davis et al, 2000). Thus, the importance of a serine at this position can not be extrapolated to other HIV-1 subtype B Vpu proteins and Vpu from other HIV-1 subtypes.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, an intact vpu gene was found to be important for the CD4 ϩ T-cell loss during infection with pathogenic SHIV (46). Current models of Vpu action suggest that by increasing viral loads, it contributes to virus spread, which in turn results in increased rates of mutation in the env and nef genes (33,45). Accumulating mutations in env would contribute positively to the development of neutralization escape variants that drive disease progression and virus transmission to a naïve host (35).…”
Section: Discussionmentioning
confidence: 99%